Les stratégies d’adaptation à la congestion automobile dans les grandes métropoles: analyse à partir des cas de Paris, São Paulo et Mumbai - Gaële Lesteven (Confins)
This PhD research studies the impact of traffic congestion in the daily life of metropolitan motorized households. Traffic congestion is defined as an internal perturbation of the automobile-based system. Adopting a systemic and comparative approach, we diagnose social, spatial and temporal characteristics of traffic congestion in the Paris region and in two mega cities of the developing world, São Paulo in Brazil and Mumbai in India. Then, we proceed to analyze the responses of public authorities, companies, organizations, and motorized households regarding traffic congestion in the three selected regions.